Regionalism in Standards: Good or Bad for Trade? - Chen, Maggie Xiaoyang; Mattoo, Aaditya (World Bank, Washington, D.C., 2013)
Regional agreements on standards have been largely ignored by economists and unconditionally blessed by multilateral trade rules. The authors find, theoretically and empirically, that such agreements increase trade between participating countries but not necessarily with the rest of the world. Adopting a common standard in a region-that is, harmonization-boosts exports of excluded industrial countries to the region. But it reduces exports of excluded developing countries, possibly because developing country firms are hurt more by an increase in the stringency of standards and benefit less from economies of scale in integrated markets. Mutual recognition agreements are more uniformly trade promoting unless they contain restrictive rules of origin, in which case intra-regional trade increases at the expense of trade with other, especially developing, countries. The authors propose a modification of international trade rules to strike a better balance between the interests of integrating and excluded countries.